A PARTICULAR COLLECTION OF SERVICE TIME DISTRIBUTIONS PARAMETERS STUDY AND IMPACT IN SOME M G SYSTEM BUSY PERIOD AND BUSY CYCLE PARAMETERS - Ferreira, Manuel Alberto M. (Acta Scientiae et Intellectus, 2024)
The problems arising when the moments of service time distributions, for which the M|G|∞ queue system busy period and busy cycle become very easy to study, are presented and it is shown how to overcome them. The busy cycle renewal function and the “peakedness” and the “modified peakedness” for the M|G|∞ busy period and busy cycle in the case of those service time distributions are also computed.